Pengaruh Kesadaran, Norma Subjektif, Razia Lapangan, dan Pemutihan Pajak terhadap kepatuhan Wajib Pajak Kendaraan Bermotor - Rustiana, I Made Lopa; Merkusiwati, Ni Ketut Lely Aryani (E-Jurnal Akuntansi; Vol 33 No 7 (2023)DO - 10.24843/EJA.2023.v33.i07.p03, 2023)
The City of Denpasar has the highest number of motorized vehicles in the Province of Bali and has had an increasing tax arrears over the last three years. This is one of the indications that taxpayer compliance in the city of Denpasar has decreased. The aim of the study was to obtain empirical evidence regarding the effect of taxpayer awareness, subjective norms, field raids, and tax deductions on motor vehicle tax compliance in the city of Denpasar. The sampling method used was accidental sampling with a sample of 100 respondents calculated using the slovin formula. Data collection using a questionnaire. The data analysis technique used is multiple linear regression. The results showed that taxpayer awareness, subjective norms, field raids, and PKB bleaching had a positive effect on motor vehicle taxpayer compliance in Denpasar City. Keywords : Awareness; Subjective Norms; Field Raids; PKB Whitening; Taxpayer Compliance.